ENGLISH MATERIAL: NEED ANALYSIS ON SECRETARY STUDENTS - Annisa Nur Fatimah (JALL (Journal of Applied Linguistics and Literacy), 2021)
This study is aimed to analyze the secretary students’ need through english material and describe kinds of English material for the secretary students. This study was descriptive analytic. The data were obtained from distributing questionnaire to the secretary students and conducting interview to the secretary students, collaborator, chief of study program of secretary and stakeholder. The data were identified in three aspects, present situation, target situation and learning situation. The data are analyzed through descriptive statistic. The results of the study are the students need on specific materials which are more relevant with their field, and more applicable in workplace.